The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12911-019-0901-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reduce diagnostic errors: a systematic review

Abstract: Background To evaluate the effectiveness of audit and communication strategies to reduce diagnostic errors made by clinicians. Methods MEDLINE complete, CINHAL complete, EMBASE, PSNet and Google Advanced . Electronic and manual search of articles on audit systems and communication strategies or interventions, searched for papers published between January 1990 and April 2017. We included studies with interventions implemented by clinicians in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 54 publications
0
46
0
2
Order By: Relevance
“…Developers seem to think that they individually should stop making errors that get through to production. Other disciplines, for example, health [41], have shown that a…”
Section: Discussionmentioning
confidence: 99%
“…Developers seem to think that they individually should stop making errors that get through to production. Other disciplines, for example, health [41], have shown that a…”
Section: Discussionmentioning
confidence: 99%
“…There is only one strategy that can be applied to decrease and nullify the effect of systematic bias: Review, criticize and modify testing procedure. (Abimanyi-Ochom et al, 2019). The authors would like to stress upon the fact that further reviewing, critical appraisal and modi ication in the testing procedure of Modi ied Jaffe's kinetic method is the need of an hour amongst the cohort of laboratory scientists and technicians.…”
Section: Figure 1: Scatter Diagram Using Pearson's Correlation Coef Imentioning
confidence: 99%
“…Diagnostic errors are common and it is estimated that everyone will experience at least one diagnostic error in their lifetime 1 . Although there is general agreement on co-or multi-morbidities complicating the diagnostic procedure resulting in higher risk for erroneous diagnoses, definitions for erroneous diagnoses lack consistency and several terms are used to refer to flawed diagnoses [2][3][4][5] . The terms misdiagnosis and overdiagnosis are often used interchangeably and they can be difficult to distinguish 3 .…”
Section: Introductionmentioning
confidence: 99%